Most and Least Helpful Events in Three Supervision Modalities. (7th December 2017) - Fickling, Melissa J.; Borders, L. DiAnne; Mobley, Keith A.; Wester, Kelly
Abstract : The authors conducted a content analysis of supervisors' ( n = 10) and supervisees' ( n = 31) descriptions ( n = 707) of most and least helpful significant events in individual, group, and triadic supervision across 1 semester. Categories by group for each modality and areas of agreement and disagreement are highlighted.